إمكانية التعرف المبكر على صعوبات التعلم لدى الأطفال في سن المدرسة باستخدام مؤشرات كفاءة النمو عند الولادة - ضو، إسماعيل ابراهيم احمد (Kulliyyah of Education, International Islamic University Malaysia, 2014)
The problem of delay in the early identification of children with learning difficulties is considered as one of the factors that lead them to suffer from poor psychological, social and educational adjustment. The purpose of this study was devising a mechanism for the early identification of children at risk of learning difficulties by using their newborn growth indicators. Additionally, it sought to determine the extent of learning difficulties among second graders and to identify any gender differences among them. Retrospective cohort study was conducted on a non-probability sample consisting of 272 children attending schools in the basic education department in Al Ojailat Libya during the academic year of 2010/2011. Data on newborn growth indicators were obtained from hospital birth records. The demographic data were collected through data form. Likewise, the teachers had to answer on a scale used to assess the behavioral characteristics of learning difficulties. The data were analyzed using the Nonparametric Statistics (i.e. Odds Ratio, Chi-Square, Kruskal-Wallis, Man-Whitney, and Cross-Tab). Results of the study have shown that there is a significant relationship between low-grade indicators on the efficiency of growth at the time of birth and learning difficulties. It also found statistically significant differences between children of low efficiency growth, and children of high efficiency growth at birth in terms of their exposure to learning difficulties, and the boys were more likely to have learning disabilities than girls. From the aforementioned findings it is recommended that schools, and hospitals need to cooperate predict the probability of early exposure of children to learning difficulties through the low efficiency indicators for growth at the time of their birth, and take the necessary early intervention steps.